Listening to neutral or self-selected motivational music during warm-up to improve short-term maximal performance in soccer players: Effect of time of day - Belkhir, Y.; Rekik, G.; Chtourou, H.; Souissi, N. (Physiology & Behavior, 2019)
The present experiment examined the effects of listening to different types of music during warm-up on the diurnal variation of short-term maximal performance (STMP) in soccer players, using a 3 × 2 mixed design with factors "Condition" (warm-up with self-selected motivational-music (WUMM) vs. warm-up with neutral-music (WUNM) vs. warm-up without-music (WUWM) and "Time of Day" (07 h00 vs. 17 h00). In a random order, twelve male soccer players performed a 5-m shuttle run test after a 10 min of WUMM, a 10 min of WUNM and a 10 min WUWM at 0 h00 and 17 h00. The higher distance (HD) and total distance (TD) were measured during the test, and the rated perceived exertion (RPE) and the feelings states (FS) were obtained immediately after the warm-up and the test. The results revealed that HD and TD were higher at 17 h00 than 07 h00 in all conditions (p < .01). At 07 h00 and 17 h00, TD and HD were higher after WUMM and WUNM than WUWM and after WUMM than WUNM (p < .01). This improvement was greater at 07 h00 than 17 h00 (e.g., 6.97% vs. 5.26% for TD). Moreover, FS were more positive after WUNM than WUWM only at 07 h00, after WUMM than WUWM at the two time-of-day (p < .01), and after WUMM than WUNM at 17 h00 (p < .01). After the 5-m shuttle run test, FS were more negative and the RPE scores were higher with WUMM than WUWM at 07 h00 (p < .01). The findings suggested that STMP and feelings depend on types of music listened during a warm-up. A warm-up with self-selected motivational-music improves STMP and feelings at 07 h00 and 17 h00 with greater enhancement in the morning. However, a warm-up with neutral-music improves STMP and feelings only at 07 h00.